2007
DOI: 10.1016/j.visres.2007.05.017
|View full text |Cite
|
Sign up to set email alerts
|

The role of interword spacing in reading Japanese: An eye movement study

Abstract: The present study investigated the role of interword spacing in a naturally unspaced language, Japanese. Eye movements were registered of native Japanese readers reading pure Hiragana (syllabic) and mixed Kanji-Hiragana (ideographic and syllabic) text in spaced and unspaced conditions. Interword spacing facilitated both word identification and eye guidance when reading syllabic script, but not when the script contained ideographic characters. We conclude that in reading Hiragana interword spacing serves as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 20 publications
10
56
1
Order By: Relevance
“…For two-fixation cases, the landing position distributions exhibited peaks at the word beginning in each font-size condition, replicating again previous results from unspaced text reading (Kajii et al, 2001;Rayner et al, 1998;Sainio et al, 2007;Yan et al, 2010) and reflecting word segmentation difficulty when reading unspaced texts (Rayner et al, 1998). The result is consistent with our previous explanation that first-of-multiple fixations at the beginning of words are indicative of a default strategy of saccade-target selection when parafoveal word segmentation failed or was not completed in time .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For two-fixation cases, the landing position distributions exhibited peaks at the word beginning in each font-size condition, replicating again previous results from unspaced text reading (Kajii et al, 2001;Rayner et al, 1998;Sainio et al, 2007;Yan et al, 2010) and reflecting word segmentation difficulty when reading unspaced texts (Rayner et al, 1998). The result is consistent with our previous explanation that first-of-multiple fixations at the beginning of words are indicative of a default strategy of saccade-target selection when parafoveal word segmentation failed or was not completed in time .…”
Section: Discussionsupporting
confidence: 89%
“…This proposal was supported empirically by a strong tendency to fixate at the word center in single-fixation cases and at the word beginning in multiple-fixation cases. Moreover, the preferred viewing location (PVL; Rayner, 1979) of the first fixation in multiple-fixation cases was at the word beginning, similar to what had been reported for reading of unspaced English text (Rayner, Fischer, & Pollatsek, 1998) and Japanese text written without word boundaries (Kajii, Nazir, & Osaka, 2001;Sainio, Hyönä, Bingushi, & Bertram, 2007). In summary, if the end of the next word is not known, the beginning of the next word may be the most informative region and therefore be selected as the primary saccade target.…”
Section: Introductionsupporting
confidence: 74%
“…Chinese natives are facilitated when reading ambiguous sentences without context (Hsu & Huang, 2000b), single-line scrolling texts (Shieh, Hsu & Liu, 2005), sentences presented with Rapid Serial Visual Presentation at high speed (Lin & Shieh, 2006), and highly complex texts with scrolling or other unusual video displays (Hsu & Huang, 2000a). Similarly, Japanese readers are facilitated by interword spacing when reading texts written exclusively in syllabic kana, but not with texts that are written in the normal mixture of kana and kanji ('Japanese characters', Sainio, Jukka, Bingushi & Bertram, 2007). However, no positive effects were found in Chinese natives reading romanised Chinese (Bassetti, 2009;Bassetti & Masterson, 2012;King, 1983).…”
Section: Effects Of Interword Spacing On Native Readers Of English Anmentioning
confidence: 99%
“…The second way is to consider the modifiers and post positions as a part of the modified word. Based on the study conducted by Saint et.al [6] using 16 subjects in Japanese reading, 60 word texts from excepts of newspapers and internet columns, it was concluded that in pure Katakana text, inter-word spacing is an effective segmentation method, in contrast to Kanji-Hiragana text, since visually silent kanji characters serve as effective segmentation uses by themselves.…”
Section: B Interword Spacing In Japanesementioning
confidence: 99%
“…Applying on the formula (7), given below, we can get the percentage of matching for target image to template image, followed by the average Euclidean distance of the collected conjunction points (6). The target character can be identified.…”
Section: E Check Matchingmentioning
confidence: 99%